DETERMINANTS OF THE INTENTION TO USE LOAN SHARKS OF STUDENTS: EMPIRICAL EVIDENCES FROM VIETNAMESE UNIVERSITIES - Anh, Khuc The; Quang, Phung Thanh (The journal of contemporary issues in business and government, 2021)
Based on the development of the Unified Theory of Acceptance and Use of Technology model (UTAUT), the authors measured the intention to use loan sharks for students in Vietnamese universities. The research utilizes both quantitative and qualitative methods with the primary data collected from students in Vietnamese universities. The results demonstrate that three main variables significantly impact on intention to use loan sharks, namely "Social Influence," "Financial Literacy," and "Expectancy Effort." In particular, the authors added the "Financial Literacy" element through the results of in-depth interviews. Besides, "Gender" and "Academic Year" also affect the relationship between three main variables and the intention to use loan sharks. Based on the research results, the authors propose several specific policy implications for authorities to eliminate loan sharks through social media and promote financial literacy in universities.